The Influence of Assessment on Civil Servant Performance Mediated by Organizational Culture in Banyuasin Regency, South Sumatra Province - Ayu, Bujang; Zunaidah, Zunaidah; Malinda, Shelfi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
This research aims to determine the moderating role of organizational culture in assessing its influence on the performance of civil servants. The sample of respondents for this research was 281 Civil Servants at Local Government Agencies of Banyuasin Regency, South Sumatra Province to collect data. Data analysis uses quantitative statistics using the Structural Equation Models program with Partial Least Squares. The results of this research show that assessment has a positive and significant effect on civil servant performance. This research also shows the moderating role of organizational culture on assessment has a positive and significant effect on civil servant performance.